Representation of Madurese Ethnic Identity in The Film Laundry Show by Rizky Balki: A Semiotics Study - SANTUSO, Santuso; SUKARNO, Sukarno; SETIAWAN, Ikwan (PT Batara Swastika Harati, 2025)
Film is a mass media capable of constructing stereotypes of a culture while shaping reality according to the producer’s intent. This study aims to describe the representation of Madurese ethnic identity in the film Laundry Show (LS) by Rizki Balki. This research is qualitative descriptive, with data consisting of dialogues, character appearances, and other codes portrayed through the character Joni. The data source is the film LS produced by PT Tripar Multivision Plus. Data collection was carried out using documentation techniques, while data analysis employed John Fiske's semiotics method, consisting of three levels of representation. The results indicate that the film LS creates a new, more positive perspective on the Madurese ethnicity. At the identity level, Joni is depicted with a distinctive language style, modern naming, contextual clothing, attractive appearance, and traits such as being humorous, multi-talented, intelligent, friendly, empathetic, religious, and having a strong work ethic. At the representation level, the use of camera techniques, lighting, and music supports this portrayal. Meanwhile, at the ideological level, Joni's identity reflects values of hard work, humanism, and religiosity as representations of the Madurese ethnicity. This study confirms that films can be an effective medium for shaping new perspectives on certain cultures.